Effect of prophylactic ankle taping on ankle and knee biomechanics during basketball-specific tasks in females. (July 2018) - Williams, Sîan A.; Ng, Leo; Stephens, Nathan; Klem, Nardia; Wild, Catherine
Abstract: Objective: The aim of this study was to investigate the effects of ankle taping on ankle and knee joint biomechanics during cutting and rebound activities in females. Design: Cross-sectional. Setting: Laboratory. Participants: Twenty semi-professional female basketball players performed a cut and rebound task under two conditions (taped and no-tape). Main Outcome Measures: Kinematic and ground reaction force data were collected during the deceleration phase of each movement task. Results: Taping resulted in a significant reduction in peak ankle dorsiflexion, inversion and internal rotation angles and range of motion (ROM) at the ankle joint; and reduced knee ROM in the sagittal plane during the rebound task only. Taping significantly reduced peak knee flexion moment (0.29 Nm/kg, P = 0.013) and increased knee internal rotation moment (0.63 Nm/kg, P = 0.026) during the cutting task compared to control. Taping also significantly reduced the internal rotation moment (0.07 Nm/kg, P = 0.025), and medial shear forces (0.14 N/kg, P = 0.012) in the rebound task. Conclusion: Results of the study suggest that ankle taping restrict ankle range of movement in the rebound task only and ankle taping appears to have upstream effects on the knee, which may have injury implications. Highlights: Ankle taping restricted ankle movement in rebound but not cutting tasks. Ankle taping restricted reduced sagittal knee movement in rebound tasks. Ankle taping affected knee kinetics during rebound and cutting tasks.